2018
DOI: 10.1111/mpp.12639
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium crown rot caused by Fusarium pseudograminearum in cereal crops: recent progress and future prospects

Abstract: Diseases caused by Fusarium pathogens inflict major yield and quality losses on many economically important plant species worldwide, including cereals. Fusarium crown rot (FCR), caused by Fusarium pseudograminearum, is a cereal disease that occurs in many arid and semi-arid cropping regions of the world. In recent years, this disease has become more prevalent, in part as a result of the adoption of moisture-preserving cultural practices, such as minimum tillage and stubble retention. In this pathogen profile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(181 citation statements)
references
References 162 publications
(268 reference statements)
3
178
0
Order By: Relevance
“…The plant pathogen Fusarium pseudograminearum is the causative agent of Fusarium crown rot (FCR) in wheat and barley, resulting in substantial yield losses worldwide (Kazan and Gardiner 2018). Particularly, in the Huanghuai wheat-growing region of China, it has been reported that F. pseudograminearum was the dominant pathogen of FCR (Li et al 2012;Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant pathogen Fusarium pseudograminearum is the causative agent of Fusarium crown rot (FCR) in wheat and barley, resulting in substantial yield losses worldwide (Kazan and Gardiner 2018). Particularly, in the Huanghuai wheat-growing region of China, it has been reported that F. pseudograminearum was the dominant pathogen of FCR (Li et al 2012;Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, F. pseudograminearum is heterothallic and it was segregated by molecular analyses (Aoki and O'Donnell 1999;Gardiner et al 2018). Like F. graminearum, F. pseudograminearum also causes Fusarium head blight (FHB) and produces deoxynivalenol (DON) mycotoxin under favorable conditions (Kazan and Gardiner 2018;Obanor et al 2013). Despite the devastating effects caused by FCR and FHB, establishing effective disease management strategies has been very difficult.…”
Section: Introductionmentioning
confidence: 99%
“…This showed that the defense mechanism of wheat to the crown rot pathogen F. pseudograminearum was complicated. Although many factors related to crown rot resistance have been identi ed, the detailed molecular mechanisms of crown rot resistance are still poorly understood [1].…”
Section: Discussionmentioning
confidence: 99%
“…F. pseudograminearum is one of the most devastating plant pathogens among soil-borne diseases. F. pseudograminearum can absorb nutrients from major winter cereals to colonize [1]. The colonization of F. pseudograminearum initiates through epidermal penetration, most often through stomatal apertures, and progresses into the parenchymatous hypoderm.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat (Triticum aestivum L.) sheath blight, a severe production constraint inducing heavy crop losses in epidemic regions, is found in almost all temperate wheat growing areas in the world and is a soil borne fungal disease caused by Rhizoctonia cerealis [1]. With the reform of planting systems, the popularization of high-yield varieties, and increases in water, fertilizer and density, the harm caused by wheat sheath blight has been become increasingly serious [2]. Hosts lack adequate resistance to wheat to sheath blight disease, thought be the results of emerging virulent pathogen populations.…”
Section: Introductionmentioning
confidence: 99%